(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
A revolutionary change occurred in India’s social and legal structure when Article 21A of the Constitution recognized education as a basic right and the Right of Children to Free and Compulsory Education Act, 2009, made it a reality. Free and compulsory education has the ability to bring about social transformation, inclusion, and equity, and this systematic analysis analyzes that possibility. This study examines the limitations and accomplishments of the rights-based education framework by drawing on academic literature, policy documents, government reports, and empirical studies released after RTE. The results show that there has been a lot of success in increasing enrollment, achieving gender parity, improving school infrastructure, and giving underrepresented groups better access, especially with the help of inclusive legislation like Section 12(1)(c). The achievement of meaningful and equitable education is, however, obstructed by enduring problems with learning outcomes, teacher ability, regional inequities, and implementation gaps. Although there has been significant progress in access to education, the assessment emphasizes that in order to fulfill education’s social mandate to transform, there must be continuous policy integration, reforms centered on quality, and alignment with the NEP 2020.